Dampak Serangan Black Hole Terhadap Protokol Routing Destination-Sequenced Distance Vector (DSDV) Dengan Model Mobilitas Random Pada MANET - Asroful Khusna Arifianto; Rakhmadhany Primananda; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile ad hoc network (MANET) is a wireless network that consists of a mobile node and has a non-fixed infrastructure. In the absence of a fixed infrastructure in MANET causes the node has an arbitrary movement. The MANET node can enter and exit the network freely, this causes MANET to be vulnerable to attacks. One of the attacks on MANET was a black hole attack. In this study using destination-sequenced distance vector (DSDV) routing as well as random waypoint mobility models and random direction models. The simulation parameters in this study are the area of ​​1000x1000m2, 700x700m2, 500x500m2, number of nodes 40, 50, 60 nodes with 5, 10, 15 and 20 black hole nodes. This study aims to determine the impact of black hole attacks on the DSDV routing protocol on random model mobility. The test parameters used are delivery ratio packages, average end-to-end delay, and normalized routing load. Based on the results of tests conducted, it was concluded that in the area of ​​1000x1000m2 and 700x700m2 the DSDV routing protocol on random waypoints had a greater impact than the DSDV routing protocol in a random direction. In the area of ​​500x500m2, the DSDV routing protocol in random direction has a greater impact than the DSDV routing protocol at random waypoints.